The effect of fungicides on vesicular-arbuscular mycorrhizal symbiosis II. The effects on area of interface and efficiency of P uptake and transfer to plant - Sukarno, N (The New phytologist, 1996)
Two experiments were conducted under controlled environmental conditions to determine the effects of the three fungicides, Benlate®. Aliette® and Ridomil®, on efficiency of P uptake from the soil and transfer across the living plant-fungal interface- of onion plants (Allium cepa L.) associated with Glomus sp. 'City Beach' (WUM 16), P applied to the soil did not apparently increase the rate of transfer (flux) of P to the plant via the fungal partner of the mytorrhiza. Benlate reduced P inflow and transfer across the interface in one of the experiments. The rate of P uptake per m living external hyphae was not affected but, as development of living external hyphae in the soil was reduced, the contribution of the fungus to P uptake was small. Aliette reduced growth of both shoots and roots, but apparently increased the accumulation of P in the tissues compared with controls. Ridomil reduced P inflow per m of root and P uptake per m living external hyphae, hut had no effect on the rate of P transfer across the interface. This led to a reduction in the overall contribution of the fungus to P nutrition